Development of xenon collisional radiative model for plasma diagnostics of Hall Effect thrusters - Rajput, Rajendrasing; Khaustova, Aloyna; Loyan, Andriy (Eastern-European Journal of Enterprise Technologies, 2017)
Hall Effect thrusters (HET) have demonstrated its applicability on satellites for the Low earth orbit (LEO), Geo-stationary earth orbit (GEO) and long duration missions. High thrust density and long lifetimes are attractive parameters of the HET. In order to improve the thruster performance and lifetimes, decades of efforts are made to understand the plasma physics. Several intrusive and non-intrusive diagnostics techniques are employed for HET investigation. Simple and precise diagnostics technique is attractive to delineate the characteristics of the thruster. Optical emission spectroscopy provides several advantages over the other methods which are used for the HET diagnostics. Using this diagnostics tool in correlation with the collisional radiative model, the information of electron kinetics is extracted instantaneously. Collisional radiative model is developed by using the xenon near-infrared emission lines. This kinetic model can be used to determine the local electron temperature with error less than 15 % for investigating the HET physics.